The Application of Brain Organoids in Assessing Neural Toxicity - Fan, Pan; Wang, YuanHao; Xu, Min; Han, Xiao; Liu, Yan (Frontiers in Molecular Neuroscience, 2022)
The human brain is a complicated and precisely organized organ. Exogenous chemicals, such as pollutants, drugs, and industrial chemicals, may affect the biological processes of the brain or its function and eventually lead to neurological diseases. Animal models may not fully recapitulate the human brain for testing neural toxicity. Brain organoids with self-assembled three-dimensional (3D) structures provide opportunities to generate relevant tests or predictions of human neurotoxicity. In this study, we reviewed recent advances in brain organoid techniques and their application in assessing neural toxicants. We hope this review provides new insights for further progress in brain organoid application in the screening studies of neural toxicants.